Doing qualitative research - Crabtree, Benjamin F.; Miller, William L. (William Lloyd) 1949- (Los Angeles SAGE Publications, Inc, 2023)
The long-awaited third edition of Doing Qualitative Research by Benjamin F. Crabtree and William L. Miller is out! Co-create your own inspired research stories with this reader-friendly text on qualitative methods, design, and analysis. Written for both students and researchers with little to no qualitative experience, as well as investigators looking to expand and refine their expertise, this clear and concise book will quickly get readers up to speed doing truly excellent qualitative research.
The first four chapters of the book set the stage by contextualizing qualitative research within the overall traditions of research, focusing on the history of qualitative research, the importance of collaboration, reflexivity, and finding the appropriate method for your research question. Each part then addresses a different stage of the research process, from data collection, data analysis and interpretation, and refocusing on the bigger picture once your research is complete. Unique chapters cover case study research, intervention studies, and participatory research. The authors use their experiences and knowledge to provide both personal and published research stories to contextualize qualitative concepts. Many of the examples demonstrate the use of qualitative methods within a mixed-methods approach. Each chapter concludes with open-ended questions to further reader contemplation and to spark discussions with classmates and colleagues.

With an abundance of clinical research examples featuring a variety of qualitative methods, Doing Qualitative Research encourages researchers to learn by doing and actively experiment with the tools and concepts presented throughout the book.-- Provided by publisher.
Includes bibliographical references (pages 379-407) and index.
Keywords: Primary care (Medicine) -- Research -- Methodology; Social medicine -- Research -- Methodology; Qualitative research; Social sciences -- Research -- Methodology